Polymersomes and their applications in cancer delivery and therapy. (September 2015) - Guan, Lijuan; Rizzello, Loris; Battaglia, Giuseppe
Polymersomes have been proposed as a platform for drug delivery systems since late 90s. They are exploited to deliver hydrophilic and/or hydrophobic therapeutic and diagnostic agents. The relatively robust membrane, the colloidal stability, along with a significant biocompatibility and easy ligands conjugation methods make polymersomes primary candidates for therapeutic drugs delivery in cancer clinical treatments. In addition, they represent an optimal choice as imaging tools in noninvasive diagnostic. As a result, polymersomes have been proposed and widely studied for anticancer treatments. However, there are not sufficient clinic translation data of human studies yet. In this critical review, we will discuss such topics, focusing on the self-assembly of membrane-forming copolymers, on their tunable physicochemical properties and on the consequential applications of these biocompatible polymersomes in drug delivery and cancer therapy.